Green technology: the enforcement of E-Waste management / Siti Aidah Wahanin and Peinita @ Nur Insyirah Peter Abdullah - Wahanin, Siti Aidah; Peter Abdullah, Peinita @ Nur Insyirah (2018)
This study focused on Green technology the enforcement of E-Waste management. It emphasised on the Mobile e-waste: Old Phones, New Life programme initiated by Malaysian Communication and Multimedia Commission (MCMC). The goals of this study are to identify the rationale for the organisation to participate in the enforcement of Ewaste management, to examine the roles of the organisation promoting enforcement of E-Waste management and to investigate the participation of community members to support the enforcement of E-Waste management through Mobile E-Waste programme. This present study obtained from secondary data to meet the above purpose of the study. The findings of primary data were only to support the secondary data regarding the enforcement of Mobile E-Waste programme. There is only 3 telecommunications industry participated in this programme in Sabah namely Digi, U-Mobile, and Maxis. The findings of both primary and secondary data outlined the pattern of environmental concern as the rationale that makes government and telecommunication player participate in E-Waste management programme to established collection box for end-of life (EOL) mobile devices and Sim-Based products. These results also reflected the support of community members for proper disposal of electronic waste if one paid incentives. Overall, the primary data support the secondary data relates to environment concern as associate reasons that makes government and telecommunication partner to participate in this programme, roles of promotion through advertising media, customer referral, and allocation of collection box at the premises to supply information. The participation of community members to support this programme was through feedback demand and comments regarding the enforcement of collection centre of Mobile E-Waste.